Supplies for the Population and Daily Life in the Nazi Occupied Lithuania - Braslauskas , Justinas (Genocidas ir rezistencija, 2016)
The aim of the article is to analyse the supplies for the population of Lithuania and aspects of everyday life in the years of the Nazi occupation. The objective is to discuss: 1) the characteristics of supplies for the population during the war years; 2) the system of supplies for the population; 3) the pricing policy applied by the Nazi occupation authorities; 4) operation of the black market during occupation years and measures by the occupation authorities against it; 5) social conditions of the urban population (manual and non-manual workers and craftsmen); and 6) the establishment of the garden allotment colonies by the urban population. Descriptive and comparative methods, analysis of sources and literature, and statistical data analysis are applied.The archival material and the press in the Nazi occupation period serve as the basis of the study. The article also draws on the available research material and other sources.The following are the conclusions of the study:1. Poor supply of food to the population of Lithuania during the Nazi occupation period was determined by the attempts of the German occupation authorities to supply food to the troops first and only then supply it to the civilian population. Equally, prioritisation of the needs of the army and the lack of materials determined poor supply of industrial products to local residents.2. The German occupation authorities organised supply of food and other products through its central system specifically designed for the war period.3. Specific characteristics of supplies for the population during the war: regular shortages of the staple food and other products, problems with transportation of products, and very small food rations issued to the population.4. The pricing policy of the occupation authorities caused destruction of the Lithuanian economy: the prices were favourable only to German officials, soldiers, etc. who had Reichsmarks, but not to the local residents. Such pricing policy was also beneficial to Germany: the population of Germany could be provided with cheap raw materials and food products at the expense of the Lithuanian population.5. The strict rationing system for food and other products by the German occupation authorities, unrealistic prices and wages determined the emergence and success of the black market. Subsequently, the black market prevented efforts of occupying forces to curb inflation and deprived the market from many food and industrial products. The occupation authorities undertook strict measures against those who participated in the black market – from penalties to the death sentences.6. The social conditions of the Lithuanian urban population (manual and non-manual workers and craftsmen) in the years of the Nazi occupation were poor. Manual workers were in a particularly difficult situation: wages could not guarantee them even subsistence minimum. The situation of non-manual workers in industry was better. The situation of craftsmen during the years of the Nazi occupation was aggravated by high taxes, shortage of auxiliary workers, and shortage of the means and raw materials for production.7. Seeking to ensure peace, the occupation authorities were looking for ways to partly improve the supply of the local population with food. One of these measures was establishment of garden allotment colonies in towns. This campaign was quite successful among the poorly supplied Lithuanian population.
Keywords: Lithuania; German occupation; domestic life; Second World War